IMPROVING STUDENTS LISTENING SKIL USING ENGLISH STORIES WITH AUDIO APPLICATION - Putri, Fadhila Bestary; Widia, Wida; Santoso, Iman (IKIP Siliwangi, 2019)
This research is a classroom action research that doing in one of SMK Kesehatan in Kabupaten Bandung Barat. Classroom action research is a research that did by teacher in the class to improve students ability in a learning teaching process, in this case their score. This research is done for maintain or solving the teaching English problems in the class. Listening skill is the one of the skill in language that important for our life. Every person starts their capability in language with great listening training. With this skill we can processing some informations and messages that tells by other person into our own understanding. Innovation in learning method such as using application in mobile phone surely can catch students attention in learning English, this teaching media can help them to improve their listening skill. And also can reduce some boredome in teaching leaning process. This research was done by using Listen English Audio Book smartphone application. This application contain the sound of narrators that telling the stories. It also contain the written text of the story which narrators tells about. The writer did a pretest before she start the treatment, the treatment itself and post test after the treatment to measure students ability in listening skill. At the pretest, the student’s average score are 4.56 move to the first post test the student’s average score increase to 6.68 and continued increase up to 7.55 at second posttest.